DEVELOPMENT OF POP-UP BOOK LEARNING MEDIA IN THE CULTURE OF BANTEN PROVINCE - Maulina, Elen; Nurhasanah, Ana; Hakim, Zerri Rahman (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
This research aims to develop and analyze pop-up book learning media on the cultural charm of Banten province, as well as to determine student responses in using pop-up book media in learning activities in class IV at SDN Banjarsari 2 Serang, which is carried out from May 2023 to by December 2023. This research uses the 4D method with the stages of defining, designing, developing and disseminating, and uses a research sample of 20 class IV students at SDN Banjarsari 2, Serang City. . This pop up book learning media on the cultural charm of Banten province received an average expert assessment of 84.3% in the